DEVELOPMENT OF ENCEPHALITIS IN COVID DISEASE - Tursunboyev Muzaffar (Web of Journals Publishing, 2025)
In this article, the development of encephalitis in covid disease, prevention of the development of encephalitis, factors causing encephalitis in COVID-19 infection and its treatment are highlighted.
Keywords: Covid disease, encephalitis, direct viral, signs of encephalitis, symptoms.